Data linkage in an established longitudinal cohort: the Western Australian Pregnancy Cohort (Raine) Study. - Mountain, J.; Nyaradi, A.; Oddy, W.; Glauert, R.; de Klerk, N.; Straker, Leon; Stanley, F. (2016)
The Western Australian Data Linkage System is one of a few comprehensive, population-based data linkage systems worldwide, creating links between information from different sources relating to the same individual, family, place or event, while maintaining privacy. The Raine Study is an established cohort study with more than 2000 currently active participants. Individual consent was obtained from participants for information in publicly held databases to be linked to their study data. A waiver of consent was granted where it was impracticable to obtain consent. Approvals to link the datasets were obtained from relevant ethics committees and data custodians. The Raine Study dataset was subsequently linked to academic testing data collected by the Western Australian Department of Education. Examination of diet and academic performance showed that children who were predominantly breastfed for at least 6 months scored higher academically at age 10 than children who were breastfed for less than 6 months. A further study found that better diet quality at ages 1, 2 and 3 years was associated with higher academic scores at ages 10 and 12 years. Examination of nutritional intake at 14 years of age found that a better dietary pattern was associated with higher academic performance. The detailed longitudinal data collected in the Raine Study allowed for adjustment for multiple covariates and confounders. Data linkage reduces the burden on cohort participants by providing additional information without the need to contact participants. It can give information on participants who have been lost to follow-up; provide or complement missing data; give the opportunity for validation studies comparing recall of participants with administrative records; increase the population sample of studies by adding control participants from the general population; and allow for the adjustment of multiple covariates and confounders. The Raine Study dataset is extensive and detailed, and can be further improved by linking to other external data sources. By linking educational outcomes to the Raine Study database, it was shown across three different age groups that a healthy diet was consistently associated with higher academic performance.